Risk factors for recurrence of ovarian endometriomas after surgical treatment: retrospective cohort study - T. S. Kachalina; M. E. Bogatova; S. S. Kuznetsov; V. F. Lazukin (Сеченовский вестник, 2020)
Aim. To identify risk factors for recurrence of ovarian endometriomas after surgical treatment.Materials and methods. The retrospective cohort study included 82 patients operated on for the first time for ovarian endometriomas, the follow-up period was 30 months. The recurrence developed in 19 patients (group 1), in 63 the recurrence was not diagnosed (group 2). Data prior to surgery (clinical characteristics, level CA-125), during surgery (cytokine concentration in peritoneal fluid, immunohistochemical analysis in capsule of ovarian endometriomas), postoperative therapy were evaluated as risk factors for recurrence. The Mann-Whitney U-test, the Fisher exact test was used to compare the groups. Specificity, sensitivity, accuracy, AUC ROC and threshold values were calculated.Results. The recurrence rate of ovarian endometriomas was 23%. There were no differences between groups according to age, proportion of smokers, body mass index, gynecological anamnesis, obstetric status and postoperative hormone therapy. Preoperative concentrations of CA-125 in group 1 were higher than in group 2: 62.5 U/ml [40.7; 112.3] vs 40.3 U/ml [20.3; 68.8], р < 0.05. The concentration of IL-6, IL-8, TNFα, IL-1β, IL-17, VEGF, MCP 1 in peritoneal fluid taken during surgery was statistically significantly higher in group 1. The highest AUC ROC was received for VEGF 0.875 (0.778–0.973) and IL-8 0.953 (0.896–1.009). For VEGF the threshold value was 125.6 pg/ml, sensitivity 100%, specificity 71%, accuracy 79.8%. For IL-8 the threshold value was 128.78 pg/ml, sensitivity 93%, specificity 87.1%, accuracy 88.9%. In group 1, higher expression values of VEGF and CD34 angiogenesis markers in ovarian endometriomas were recorded. The highest AUC ROC was noted for CD34 — 0.844 (0.683–1.000), threshold value was 2.5%, sensitivity 90%, specificity 75%, accuracy 80.8%.Conclusion. Risk factors for recurrence of ovarian endometriomas after operative treatment include VEGF and IL-8 levels in peritoneal fluid and expression of CD34 in the capsule.